2017
DOI: 10.18203/2320-6012.ijrms20175430
|View full text |Cite
|
Sign up to set email alerts
|

Burnout among nurses working in critical care settings: a case of a selected tertiary hospital in Rwanda

Abstract: INTRODUCTIONBurnout is characterized by loss of emotional strength, not valuing human beings living together with or offering service and decreased in job performance and success due to lack of interest related to occupational stressors.1Burnout was recognized as work related danger among human oriented professionals including health care professionals since they are required to work many hours to help humans and face a challenge of high demand and low resources.1 Burnout is due to prolonged work related stres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
11
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 28 publications
(50 reference statements)
5
11
2
Order By: Relevance
“…The majority of the participants (25.7 %) with diploma in nursing were found to have high level of burnout, The reason may be due to the health policy in hospitals, where the diploma level is the weakest part of the group. Therefore, the level of burnout is high this result agree with study conducted in Iran in 2017 entitled ( Burnout among nurses working in critical care settings: a case of a selected tertiary hospital in Rwanda) (18) .…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The majority of the participants (25.7 %) with diploma in nursing were found to have high level of burnout, The reason may be due to the health policy in hospitals, where the diploma level is the weakest part of the group. Therefore, the level of burnout is high this result agree with study conducted in Iran in 2017 entitled ( Burnout among nurses working in critical care settings: a case of a selected tertiary hospital in Rwanda) (18) .…”
Section: Discussionsupporting
confidence: 89%
“…Most of the participants were male, and this indicates that these results differ from many of the studies that were conducted, which showed that the percentage of females is more than males, this agree with the study conducted in 2013 by Ayala and Carnero (17) . This study found that there is a high rate of burnout in the health care workers during the COVID 19 pandemic this agree with (18) The reason may be a lack of experience in dealing with such an epidemic, as well as a lack of personal equipment to deal directly contact with COVID19 patients.…”
Section: Discussionsupporting
confidence: 80%
“…Most of the participants were male, and this indicates that these results differ from many of the studies that were conducted, which showed that the percentage of females is more than males, this agree with the study conducted in 2013 by Ayala and Carnero (17) . This study found that high level of burnout among health workers during the COVID 19 pandemic this agree with (18) The reason may be a lack of experience in dealing with such an epidemic, as well as a lack of personal equipment to deal directly contact with COVID19 patients.…”
Section: Discussionsupporting
confidence: 74%
“…[8] Furthermore, workplace stress can lead to poor quality of nursing care, which may negatively impact the patients' outcomes. [9] Moreover, when workplace stress is not well controlled, it can negatively affect the institution by impairing the normal daily activities , decreasing productivity, increasing absenteeism and turnover among the employees; this information, shows the urgency of exploring the possible causes of job stress and coping strategies. [1] The coping strategies to curb the workplace stress are identified in the literature; the common coping strategy that are applied by the ICU nurses to control the workplace stress are recreation activities.…”
Section: Introductionmentioning
confidence: 99%